The current region control strategy with wide speed range of radial-axial consequent pole hybrid excitation machine for electric vehicles - Wang, Xu (2023)
A radial-axial consequent pole hybrid excitation machine (RACP-HEM) with the advantages of interior permanent magnet synchronous machine (IPMSM) and electric excitation machine is studied, which has high torque output and wide speed range for electric vehicles (EVs). The radial-axial d-q axis model is established to solve the problem that the inherent asymmetry of the airgap density of consequent pole leads to difficult mathematical modeling. The current region control strategy with torque and speed as the criteria is proposed to efficiently improve operation performance of the RACP-HEM, which divides the operation region into different modes to realize high output torque and wide speed region. The maximum torque per ampere (MTPA) control of armature and excitation currents is integrated with the advantages of AC excitation and compared with id=0 control for low-speed region to obtain higher output torque. In high-speed region, the hybrid advanced angle field weakening control with three-dimensional (3-D) current vector is adopted to utilize the excitation current to solve the problem of the field weakening out of control caused by the traditional voltage feedback field weakening control to achieve higher speed. Finally, the simulation results and prototype experiments verify the effectiveness of the proposed control strategy for RACP-HEM.